Modern competitive analysis - Oster, Sharon M. (New York : Oxford University Press, 1994)
This revised edition presents an up-to-date analysis of management strategy, integrating a wide spectrum of ideas. Using many examples from organizations and non-profit groups, the text uses recent theories to illuminate situations faced by businesses today.
Includes bibliographical references (p. 355-389) and index.
Keywords: Competition; Strategic planning